Pengujian Gasifikasi Updraft Untuk Tongkol Jagung dan Cangkang Mete Sebagai Sumber Energi Alternatif - Taufik, Muhamad Rian; Mangalla, Lukas Kano; Barata, La Ode Ahmad (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2021)
Gasification is the process of  converting energy from fuel containing carbon (solid or liquid) into a gas called syngas (synthesis gas). The purpose of this study was to determine the characteristics of  syngas resulting from the gasification of a mixture of corn cobs and cashew shells and to determine the ideal composition  of  a  mixture  of  corn  cobs  and  cashew  shells  that  produces  optimal  gas  ingredients.  The method  used  in  this  study  is  an  experimental  method  by  making  a  gasification  tool  and  taking  data directly with several variations of composition. The results showed that thecharacteristics  syngas at the composition of 100% corn cobs could not produce flames, the mixture composition of 75% corn cobs and 25% cashew shells could not produce flames, at the composition of a mixture of 50% corn cobs and 50% cashew shells it was able to produce flames. flame, the composition of a mixture of 25% corn cobs and 75%  cashew  shells  can  already  produce  a  flame  and  a  composition  of  100%  cashew  shells  can  also produce a gasification flame. Virtually the resulting flame is thought to be due to the presence of more hydrogen  (gas)  than  carbon  (smoke  from  combustion).  The  best  composition  in  updraft  gasification testing for corn cobs and cashew shells was obtained in a composition with a mixture of 25% corn cobs and 75% cashew shells, the resulting flame was obtained at 32.5 minutes to 50 minutes. Key words: Updraft gasification, composition , corn cobs, cashew shells, flame